Does Leader-Member Exchange Impact on Organizational Citizenship Behaviour Readiness? Evidence from State Government Agency - Rashidah Mohamad Ibrahim; Mazuri Abd Ghani; Noorul Hafizah Hashim; Aziz Amin (International Review of Management and Marketing, 2017)
Local Government (LG) being the third-tier in Malaysian government has been identified as one of the government agencies mandated to drive economic growth and development of a district and its residents. Being one of the main service providers, LG has yet to meet the public expectations as many complaints have being filed towards its operational issues as evidenced from statistical data from Public Complaint Bureau (PCB). Thus, in responding to PCB statistics and lack in-depth research on LG, this paper aims to investigate the relationship between Leader-Member Exchange (LMX) and Organizational Citizenship Behaviors (OCB) among local governments' employees working in Southern region of Malaysia. Multiple regression analysis from a data set of 222 respondents, after factor analysis, revealed that LMX-AffectRespect and LMX-Contribution have positive impact towards OCB while LMX-Loyalty was found to be insignificant. A moderate 54% of variance in OCB has been explained. This study has provided empirical insights in supporting social exchange theory that quality LMX relationship has the ability to invoke OCB readiness. Due to local governments constant interactions with the public, enhancement in dyadic relationship can help in reducing the level of complaints and towards improving the much needed operational efficiency.